PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI - ODELIA LIOENY; MARIA MARIA (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to obtain an empirical evidence about the influence of company characteristics on firm value of non-financial company listed on IDX. The variables used on this study are firm size, firm age, dividend policy, profitability, liquidity, leverage, managerial ownership and institutional ownership as independent variables and firm value as a dependent variable.This study used non-financial companies that listed on Indonesia Stock Exchange (IDX) during the research period from 2017 to 2020 as an object. There are 51 companies that met the criteria, where the samples are selected by using purposive sampling method. The result of this study shows that firm size, firm age, profitability, and leverage have an effect on firm value while the other variables such as dividend policy, liquidity, managerial ownership, and institutional ownership have no effect on firm value